2009
DOI: 10.1016/j.cell.2009.02.009
|View full text |Cite
|
Sign up to set email alerts
|

The Spliceosome: Design Principles of a Dynamic RNP Machine

Abstract: Job Sharing and Cooperation between RNAs and Proteins RNPs are involved in a large spectrum of molecular activities. Whereas assemblies such as the signal recognition particle or the U7 snRNP serve as adaptors or transport devices, other

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
2,647
0
41

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 2,304 publications
(2,716 citation statements)
references
References 134 publications
28
2,647
0
41
Order By: Relevance
“…Fourth, highly purified, fully assembled U2 or U4/U6•U5 tri-snRNP was capable of significant rescue of the CoilMO phenotype, whereas U1 snRNP was not. This suggests that stable U2 snRNP interactions with pre-mRNA, which trigger spliceosome assembly 6 , represent a rate-limiting step in embryonic gene expression. Because neither the snRNP proteins nor the snRNAs alone had rescuing ability and only mature assembled snRNPs were active, we conclude that macromolecular assembly of snRNPs is the essential function of coilin in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fourth, highly purified, fully assembled U2 or U4/U6•U5 tri-snRNP was capable of significant rescue of the CoilMO phenotype, whereas U1 snRNP was not. This suggests that stable U2 snRNP interactions with pre-mRNA, which trigger spliceosome assembly 6 , represent a rate-limiting step in embryonic gene expression. Because neither the snRNP proteins nor the snRNAs alone had rescuing ability and only mature assembled snRNPs were active, we conclude that macromolecular assembly of snRNPs is the essential function of coilin in zebrafish embryos.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly to the tri-snRNP, intermediates in mature U2 snRNP formation can be trapped in CBs upon knockdown of appropriate assembly factors 17 . U2 snRNP is present in cells in 12S and 17S forms, reflecting the association of the core U2 snRNP containing the Sm ring U2A and U2B proteins (12S) with the SF3 complex (17S) 5,6 . Notably, both the 12S and 17S forms of the U2 snRNP rescued coilin morphants equally, indicating that formation of the 12S U2 snRNP is compromised upon coilin depletion.…”
Section: Discussionmentioning
confidence: 99%
“…Recruitment of the U5 snRNP by the spliceosome is required for its catalytic activity. 1 RNA immunoprecipitation experiments using an anti-PRP6 antibody revealed that knockdown of SND1 correlated with a decreased recruitment of the U5 snRNP on the CD44 pre-mRNA in PC3 cells (Figure 5c), indicating that SND1 favors assembly of the active spliceosome. Moreover, SAM68 was also shown to associate with the U5 snRNP under conditions in which exon v5 inclusion was induced, 50 and we found that knockdown of SND1 strongly reduced the association of SAM68 with the CD44 pre-mRNA (Figure 5d).…”
Section: Identification Of Snd1 As a Novel Sam68-interacting Proteinmentioning
confidence: 99%
“…This phenomenon is driven by a large macromolecular complex, the spliceosome, composed of five small nuclear ribonucleoproteins (snRNPs) and over 200 auxiliary proteins. 1 In higher eukaryotes, a large number of exons can be alternatively spliced to yield different transcripts from a single gene, thereby increasing the coding potential of the genome. 2,3 Indeed, the large majority of multi-exon human genes undergo alternative splicing (AS) to produce at least two mRNA variants.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of these molecular devices are based on nucleic acid scaff olds, for example, riboswitches 1 , ribozymes 2 , transposons 3 , ribosomes 4 , cis -regulatory elements on DNA 5 , spliceosomes 6 , to name a few. Owing to the specifi city and predictability of Watson-Crick base pairing, engineerability and the ability to form a rich repertoire of unusual structures based on their sequence and external triggers, nucleic acids have proven to be a remarkably powerful scaff old to build a variety of programmable synthetic nanomachines 7 .…”
mentioning
confidence: 99%